Effects of Display Curvature, Presbyopia, and Task Duration on Visual Fatigue, Task Performance, and User Satisfaction. - Choi, Donghee; Kyung, Gyouhyung; Nam, Kyunghyun; Park, Sungryul (Human Factors, 2019)
Objective: This study examined the effects of display curvature, presbyopia, and task duration on visual fatigue, task performance, and user satisfaction.Background: Although curved displays have been applied to diverse display products, and some studies reported their benefits, it is still unknown whether the effects of display curvature are presbyopia-specific.Method: Each of 64 individuals (eight nonpresbyopes and eight presbyopes per display curvature) performed four 15-min proofreading tasks at one display curvature radius setting (600R, 1140R, 4000R, and flat; mm). Diverse measurements were obtained to assess visual fatigue, task performance, and user satisfaction.Results: The mean pupil diameter was the largest with 1140R, indicating this curvature radius was associated with the least development of visual fatigue; 600R was comparable with 1140R in terms of pupil diameter. The presbyopic group showed a 28.5% slower proofreading speed compared with the nonpresbyopic group, whereas their proofreading accuracy was comparable. For both groups, the mean visual fatigue increased significantly during the first 15 min of proofreading, as indicated by a decrease of 0.11 mm in the mean pupil diameter, an increase of 3.8 in the mean bulbar conjunctival redness, and an increase of 9.13 in the mean eye complaint questionnaire score.Conclusion: The effect of display curvature was not presbyopia-specific. Low visual fatigue was observed with 1140R and 600R.Application: Display curvature radii near or in the range of 600R and 1140R and frequent breaks are recommended for both presbyopic and nonpresbyopic groups to reduce their visual fatigue due to visual display terminal tasks.